Development of STEM-based Virtual Laboratory on Global Warming Topic for Junior High School Student - Zusje Wiesje Merry Warouw; Witha Christine Aprilya Wekes; Fransiska Harahap; Widya Anjelia Tumewu; Brian Ricard Wola (Jurnal Penelitian Pendidikan IPA, 2024)
Our study aimed to develop a feasible STEM-based virtual laboratory on global warming topics for junior high school students. We used the development research type by adopting Thiagarajan's 4D model development procedure, which was limited to the development stage. The data collection methods we used were questionnaires and interviews, while the research instruments were interview sheets and questionnaires. Product validation involved a lecturer as a subject matter expert and a lecturer as a learning media expert. In addition, a small group evaluation sample with 10 students was selected using a simple random sampling technique to be involved in the product trial. Qualitative and quantitative data analysis techniques were used. The results showed that the assessment by subject matter experts received a feasibility percentage of 84%, including the criteria worth using, and the assessment by learning media experts received a feasibility percentage of 85%, including the criteria worth using. In addition, the small group student response trial showed 91%, which means the developed product is very practical. Thus, the STEM-based virtual laboratory on global warming topics was declared feasible for junior high school students to use in science learning